Translation as a catalyst for foreign language learning: a self-regulated learning approach mediated by instructor feedback and peer collaboration - Chun Li; Kizito Tekwa (Humanities & Social Sciences Communications)
Abstract This research was undertaken against the backdrop of the realization—albeit with scanty empirical evidence—that trainee translators do not always possess the much-needed foreign language (FL) proficiency to excel in the profession upon graduation. The study describes how a semester-long graduate-level computer-assisted translation (CAT) course was designed to improve the FL proficiency of 19 trainees (12 female and 5 male), whose FL knowledge, or lack thereof, was determined using a pre-study questionnaire to gather data on perceived FL proficiency, years of FL learning, and number of pertinent courses taken. The CAT course, informed by the questionnaire findings, was grounded in the constructivist learning approach, which foregrounded self-regulated learning (SRL), peer collaboration, and scaffolded instructions and feedback. Based on data gathered from the trainees’ collaboratively translated texts, post-study questionnaire results, and SRL logs, it was found that the trainees’ grammar, writing, vocabulary, and delivery errors significantly reduced as they translated more content. These practical implications of the study’s findings are crucial for understanding of FL’s place in and successful incorporation into translation programs and course designs.